Investigating mitochondrial dysfunction in gestational diabetes mellitus and elucidating if BMI is a causative mediator. (August 2020) - McElwain, Colm; McCarthy, Cathal M.
Abstract: Objective: Gestational diabetes mellitus (GDM) is defined as any degree of glucose intolerance which is diagnosed during pregnancy and poses considerable health risks for mother and child. Maternal body mass index (BMI) correlates with GDM diagnosis and the pathophysiology of this link may be explained through oxidative stress and mitochondrial dysfunction. In this study we investigate if mitochondrial dysfunction is evident in GDM by measuring cell free mitochondrial DNA concentration and determine if a potential relationship exists between maternal mitochondrial function and GDM diagnosis. Study design: Plasma samples were taken at 20 weeks' gestation from women who subsequently developed GDM (n = 44) and matched with women with uncomplicated pregnancies (n = 85) as controls. Control group 1 was matched by maternal age and BMI (n = 41) to GDM cases, while control group 2 was matched by maternal age alone (n = 44). Prediction potential was determined by binary regression analysis. Statistical analysis was performed on SPSS Statistics v25. Results: Binary regression analysis showed a statistically significant association between mtDNA concentration and GDM diagnosis (p = 0.032) in GDM cases versus control group 2, indicating that GDM patients have higher circulating mtDNA concentrations relative to healthy control patients. The lack of statistical significance in control group 1 suggests that BMI may be linked to mitochondrial function in GDM patients. Conclusion: These results demonstrate a potential pathogenic role for mitochondrial dysfunction in GDM, with BMI presenting as a likely physiological mediator.